9x+3y=3

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 9x from both sides of the equation.

3y=3-9x

Divide each term by 3 and simplify.

Divide each term in 3y=3-9x by 3.

3y3=33+-9×3

Cancel the common factor of 3.

Cancel the common factor.

3y3=33+-9×3

Divide y by 1.

y=33+-9×3

y=33+-9×3

Simplify 33+-9×3.

Simplify each term.

Divide 3 by 3.

y=1+-9×3

Cancel the common factor of -9 and 3.

Factor 3 out of -9x.

y=1+3(-3x)3

Cancel the common factors.

Factor 3 out of 3.

y=1+3(-3x)3(1)

Cancel the common factor.

y=1+3(-3x)3⋅1

Rewrite the expression.

y=1+-3×1

Divide -3x by 1.

y=1-3x

y=1-3x

y=1-3x

y=1-3x

Reorder 1 and -3x.

y=-3x+1

y=-3x+1

y=-3x+1

y=-3x+1

Using the slope-intercept form, the slope is -3.

m=-3

Find the Slope 9x+3y=3